Adaptive innate immunity or innate adaptive immunity?. (17th July 2019) - Černý, Jan; Stříž, Ilja
Abstract : The innate immunity is frequently accepted as a first line of relatively primitive defense interfering with the pathogen invasion until the mechanisms of 'privileged' adaptive immunity with the production of antibodies and activation of cytotoxic lymphocytes 'steal the show'. Recent advancements on the molecular and cellular levels have shaken the traditional view of adaptive and innate immunity. The innate immune memory or 'trained immunity' based on metabolic changes and epigenetic reprogramming is a complementary process insuring adaptation of host defense to previous infections. Innate immune cells are able to recognize large number of pathogen- or danger- associated molecular patterns (PAMPs and DAMPs) to behave in a highly specific manner and regulate adaptive immune responses. Innate lymphoid cells (ILC1, ILC2, ILC3) and NK cells express transcription factors and cytokines related to subsets of T helper cells (Th1, Th2, Th17). On the other hand, T and B lymphocytes exhibit functional properties traditionally attributed to innate immunity such as phagocytosis or production of tissue remodeling growth factors. They are also able to benefit from the information provided by pattern recognition receptors (PRRs), e.g. γδT lymphocytes use T-cell receptor (TCR) in a manner close to PRR recognition. Innate B cells represent another example of limited combinational diversity usage participating in various innate responses. In the view of current knowledge, the traditional black and white classification of immune mechanisms as either innate or an adaptive needs to be adjusted and many shades of gray need to be included.